The Influence Of Leadership And Competency On The Performance Of Civil Service Agency Employees And Human Resources Development In The City Of Banda Aceh - Najmi Suhaily; Wirman Syafri; Dyah Poespita Ernawati; Andi Masrich (Sean Institute, 2024)
The performance of the Banda Aceh City Personnel and Human Resources Development Agency is still achieving programs and activities below targets and employee attendance is still not good. The overall quality of employee work is still not optimal. In this regard, the competencies needed to achieve performance include effective leadership and employees who have good performance. So leadership and competence will influence performance. This research aims to analyze the influence of leadership (X1) and competence (X2) on employee performance (Y) at the Banda Aceh City Personnel and Human Resources Development Bureau. The sample was obtained using a purposive sampling method, and 44 civil servant respondents were selected. The method used is a quantitative approach with a survey method. The data analysis technique uses path analysis. The results of the analysis show that leadership and competence have a significant partial or simultaneous effect on employee performance. Leadership contributes 27.8% to employee performance, while competence contributes 48.0% to employee performance. Thus, leadership and employee competency have a significant simultaneous effect on the performance of employees of the Banda Aceh City Personnel and Human Resources Development Agency amounting to 75.8% while the remaining 24.2% is influenced by other variables not studied such as work discipline, organizational culture, work motivation